(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Earthquakes signal a change in the earth’s internal structure. Seismic activity is frequent in most places of the world, albeit the frequency with which it occurs is dependent on the tectonic configuration of the area. Previous earthquakes have resulted in significant loss of life and property, impacting a country’s social and economic conditions. Though an earthquake cannot be avoided, the least that can be done to minimise damage is to make buildings earthquake resistant. As our understanding of earthquakes has improved, most countries have enforced the inclusion of seismic precautions in building design and architecture. In the event of an earthquake, seismic waves from the epicentre are propagated across the entire region. The effects of lateral loads like as earthquake loads, wind loads, and blast forces have been a major issue in recent years. One of the key issues that every designer faces is providing sufficient strength and stability in the face of lateral stresses. As a result, structural engineers must have a thorough understanding of the seismic performance of various types of shear walls in order to protect the structure against lateral loads. For (G+20) story’s, the current paper compares the seismic performance of high rise structures and optimizes the thickness of RCC shear wall, Steel Plate Shear Wall (SPSW), and composite shear wall. The design and analysis of the building with RCC shear wall, steel plate shear wall and composite shear wall is carried out using software ETABS or STAADPRO. Effect of varying thickness of shear panels and comparison of the results of story drift and story shear is presented. The main goal of this project is to use STAAD Pro to study and design a multi-story structure [G + 2 (3 dimensional frame)]. The design entails load calculations and a STAAD Pro analysis of the entire structure. Limit State Design, as defined by the Indian Standard Code of Practice, was employed in the STAAD.Pro analysis. STAAD.Pro comes with a cutting edge user interface, visualization tools, and sophisticated analysis and design engines that can do complex finite element and dynamic analysis. STAAD.Pro is the professional’s choice for model generation, analysis, and design, as well as visualisation and result verification. Initially, we evaluated and constructed a G + 1 story building [2-D Frame] for all load combinations [dead and live].STAAD.Pro offers a very user-friendly interface that allows users to sketch the frame and enter load values and dimensions. The structure is then analyzed and members with reinforcement details for RCC frames are designed based on the supplied criteria. The accurate analysis and design of a G + 2 3-D RCC frame under various load combinations is the final job. A 3-D RCC frame with three bays has been considered. G + 2 floors made up the y-axis. Each floor has 137 beams and 140 columns, for a total of 137 beams and 140 columns. The ground floor was 3.5 meters tall, and the other two story’s were also 3.5 meters tall. Under self-weight, dead load, and live load conditions, the structure was tested. The ground floor height was 3.5m and rest of the 2 floors had a height of 3.5m.The structure was subjected to self weight, dead load, live load under the load case details of STAAD.Pro. The materials were specified and cross-sections of the beam and column members were assigned.The fixed supports at the structure’s base were also defined. For design purposes, the codes of practice to be followed were also stated, along with other relevant aspects. The structure was then analyzed and the members were designed using STAAD.Pro. After completing the design, we may work on the structure and investigate the bending moment and shear force values using the generated diagrams in the post-processing mode. We’ve also looked at the deflection of different parts under various loading scenarios. The building’s design is dictated by the minimum standards set forth in the Indian Standard Codes. Building structural safety regulations are set to the bare minimum. Are being covered by way of laying down minimum design loads which have to be assumed for dead loads, imposed loads, and other external loads, the structure would be required to bear. Strict conformity to loading standards recommended in this code, it is hoped, will ensure the structural safety of the buildings which are being designed. Structure and structural elements were normally designed by Limit State Method. Complicated and high-rise structures need very time taking and cumbersome calculations using conventional manual methods. STAAD.Pro provides us a fast, efficient, easy to use and accurate platform for analysing and designing structure.